Samuel Chester Reid family papers - Reid, Samuel Chester, 1783-1861.; Reid, Samuel C. (Samuel Chester), 1818-1897.
Correspondence, diaries, journals, speeches, writings, biographical and genealogical material, financial and legal papers, newspaper clippings, scrapbooks, maps, lithographs, and other papers. Subjects include the claim filed by Samuel Chester Reid (1783-1861), captain of the privateer General Armstrong, in connection with scuttling the privateer in a battle with British warships at Faial Island, Azores, during the War of 1812; Reid's recommendation for the design of the U.S. flag; the Mississippi Valley & Brazil Steamship Company, St. Louis, Mo., founded by Reid and others in 1874 to provide river and ocean freight between St. Louis and Rio de Janeiro, Brazil; the activities of Samuel Chester Reid (1818-1897) in Ben McCulloch's Texas Rangers during the Mexican War and as a correspondent in the South during the Civil War; John Rowan and his residence, Federal Hill, Bardstown, Ky.; and activities of the U.S Army 6th Cavalry stationed in Texas, 1866-1868.
Family correspondents include members of the Jennings, Reid (Reed), and Rowan families. Other correspondents include James Buchanan, Aaron Burr, John M. Clayton, Grover Cleveland, Samuel W. Dabney, Millard Fillmore, J. M. Gorden, G. W. Grannis, Rutherford Birchard Hayes, George Wallace Jones, Amos Kendall, Charles W. March, Francis Markoe, E. E. McKay, Charles O'Conor, Franklin Pierce, Rodman M. Price, Daniel Webster, Fletcher Webster, and P. H. Wendover.
Library of Congress Prints and Photographs Division.
Library of Congress Geography and Map Division.
Family members represented include Samuel Chester Reid (1783-1861), naval officer, and his son, Samuel Chester Reid, lawyer, (1818-1897).
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Buchanan, James, -- 1791-1868 -- Correspondence; Burr, Aaron, -- 1756-1836 -- Correspondence; Clayton, John M. -- 1796-1856 -- Correspondence; Cleveland, Grover, -- 1837-1908 -- Correspondence; Dabney, Samuel W. -- Correspondence; Fillmore, Millard, -- 1800-1874 -- Correspondence; Gorden, J. M. -- Correspondence; Granniss, G. W. -- Correspondence; Hayes, Rutherford Birchard, -- 1822-1893 -- Correspondence; Jones, George Wallace, -- 1804-1896 -- Correspondence; Kendall, Amos, -- 1789-1869 -- Correspondence; March, Charles W. -- 1815-1864 -- Correspondence; Markoe, Francis, -- 1801-1871 -- Correspondence; McCulloch, Ben, -- 1811-1862.; McKay, E. E. -- Correspondence; O'Conor, Charles, -- 1804-1884 -- Correspondence; Pierce, Franklin, -- 1804-1869 -- Correspondence; Price, Rodman M. -- 1816-1894 -- Correspondence; Rowan, John, -- 1773-1843.; Rowan, John, -- 1773-1843 -- Homes and haunts; Webster, Daniel, -- 1782-1852 -- Correspondence; Webster, Fletcher, -- 1813-1862 -- Correspondence; Wendover, P. H. -- 1768-1834 -- Correspondence; Jennings family -- Correspondence; Reed family; Rowan family -- Correspondence; United States. -- Army. -- Cavalry, 6th.; United States. -- Navy -- History -- War of 1812.; General Armstrong (Privateer); Mississippi Valley and Brazil Steamship Company; Texas Rangers; Dwellings -- Kentucky -- Bardstown; Flags -- United States; Mexican War, 1846-1848.; Brazil -- Commerce -- United States; Confederate States of America -- History; Faial Island (Azores) -- History; Rio de Janeiro (Brazil) -- Commerce; Saint Louis (Mo.) -- Commerce; United States -- Commerce -- Brazil; United States -- History -- War of 1812 -- Naval operations; United States -- History -- Civil War, 1861-1865 -- Journalists; Naval officers